Republic of Tajikistan : Staff Report for the 2002 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2003)
This paper evaluates Tajikistan's 2002 Article IV Consultation and a Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). Tajikistan's previous IMF-supported program went off track in mid-2001 largely because of poor progress with structural reform and weak management of external debt. To revitalize the reform process, the authorities satisfactorily implemented a Staff-Monitored Program that covered the first half of 2002. The IMF staff commends the authorities for the progress in economic areas realized over the past few years, and supports the authorities' request for a new three-year PRGF arrangement.